Breaking Barriers: How Women’s Transformational Leadership Enhances Educational Quality - Rubini, Rubini (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This research aims to examine the role of women’s transformational leadership in enhancing educational quality at the International Islamic School. The study examines how female leadership, grounded in transformational principles, fosters both academic excellence and the integration of Islamic values in education. Despite the increasing presence of women in leadership roles, there is limited research on how their leadership styles impact educational outcomes in Islamic institutions. Utilizing a qualitative approach, this case study analyzes interviews, document reviews, and literature-based case studies with Thematic analysis. The findings reveal that women’s transformational leadership has a positive impact on educational quality by fostering a vision of academic and moral development, engaging stakeholders, and overcoming gender barriers. The leadership promotes an inclusive environment, encourages professional growth, and ensures the integration of Islamic values into modern curricula. The study contributes valuable insights into the intersection of leadership, gender, and education in Islamic contexts, offering recommendations for promoting transformational leadership among women in educational institutions. This research highlights the importance of adopting leadership practices that strike a balance between academic rigor and religious principles in faith-based schools.